The Moderating Role of Self Efficacy on the Perceptions of Justice and Turnover Intentions - AŞKUN, OLCAY BİGE (ELSEVIER SCIENCE BV, 2016)
Previous research in organizational behavior has reported many variables serving as either mediators or moderators in the predictive relationship between justice perceptions and turnover intentions. So far, none of the studies seems to have considered the possible influence of self-efficacy as a moderating variable in that relationship. Positive organizational behavior approach strongly offers usage of individual capacity variables for producing positive organizational outcomes (Luthans, 2002). In this study, we have explored the moderating role of self-efficacy in the relationship between justice perceptions and turnover intentions. Nine-hundred and four employees coming from private companies of Istanbul and Ankara, in Turkey, participated in the study. To analyze the results, we have used confirmatory factor analyses and regression analyses. Our results revealed important findings in relation to the moderating effects of different self-efficacy dimensions. We have found a negative relationship between justice perceptions and turnover intentions. For self-efficacy dimensions, many interaction effects were as expected, except for those high in willingness to expend effort in completing the behavior. We discussed the results in light of certain theoretical assumptions and offered related recommendations for organizational practice and future research. (C) 2016 The Authors. Published by Elsevier Ltd.
Keywords: Self Efficacy; Perceptions of Justice; Turnover Intentions; ORGANIZATIONAL JUSTICE; DISTRIBUTIVE JUSTICE; PROCEDURAL JUSTICE; SCALE; RESPONSES